BIOACTIVE COFFEE COMPOUNDS SYNERGISTICALLY ENHANCE THE ANTITUMOR EFFECTS OF CHEMO AND IMMUNOTHERAPY FOR HEPATOCELLULAR CARCINOMA IN VITRO - Cardoso, Leticia Valente [UNESP]; Riechelmann, Luana Casarin [UNESP]; Fernando, Luis Barbisan [UNESP]; Ribeiro, Guilherme Romualdo [UNESP] (Elsevier, 2025)
Introduction and Objectives Hepatocellular Carcinoma (HCC) yields high global incidence and mortality rates and an unfavorable prognosis. Although current therapies for advanced HCC are promising, their outcomes remain limited. In this context, there is increasing interest in innovative strategies, such as combining bioactive compounds (BCs) with chemo- and immunotherapies. BCs in coffee have stood out due to their chemopreventive effects reported in epidemiological and experimental studies. However, their antitumor potential, particularly in combination with conventional therapies, remains incompletely understood. In this study, we investigated whether coffee-derived compounds could enhance the antitumor effects of sorafenib (SOR) and atezolizumab plus bevacizumab (ATZ+BVZ) in vitro. Materials and Methods LX2 hepatic stellate cells and HepG2/C3A (HCC) cells were cultured in 3D (spheroids) and 2D (transwell) systems, and treated with caffeine (CAF), trigonelline (TRI), chlorogenic acid (CGA), caffeic acid (CA), kahweol (KWL), SOR, ATZ, and BVZ for 24 and 48 h for half maximum effective concentration (EC50) determination (MTT/LDH assays). Next, the coffee compounds were combined with SOR or ATZ+BVZ at sub-effective and physiologically plausible EC50 fractions (1/5, 1/6, or 1/10) and evaluated by MTT (3D), scratch (migration), and colony formation assays (2D), with combination index calculation. Results CGA, CA, and TRI showed antagonistic effects to the therapies. In contrast, CAF or KWL synergistically enhanced the anti-tumor effects of SOR and ATZ plus BVZ in reducing spheroid viability. The combination of CAF plus KWL further intensified the anti-tumor effects of both treatments, also inhibiting colony formation and cell motility. Conclusions These findings suggest that coffee-derived compounds may strengthen the therapeutic efficacy against HCC. Further experiments include in vitro metabolomics and transcriptomics, and in vivo xenograft mouse model.